The Swerve and Ancient Materialism - Nail, Thomas; Kolozova, Katerina (Identities, 2022)
Author(s): Thomas Nail and Katerina Kolozova Title (English): The Swerve and Ancient Materialism Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 58-71 Page Count: 13 Citation (English): Thomas Nail and Katerina Kolozova, “The Swerve and Ancient Materialism,” Identities: Journal for Politics, Gender and Culture, Vol. 19, No. 1-2 (2022): 58-71.